Influences of the Antarctic Ozone Hole on Southern Hemispheric Summer Climate Change - Bandoro, Justin; Solomon, Susan; Donohoe, Aaron; Thompson, David W. J.; Santer, Benjamin D. (Journal of Climate, 2014)
Over the past three decades, Antarctic surface climate has undergone pronounced changes. Many of these changes have been linked to stratospheric ozone depletion. Here linkages between Antarctic ozone loss, the accompanying circulation changes, and summertime Southern Hemisphere (SH) midlatitude surface temperatures are explored. Long-term surface climate changes associated with ozone-driven changes in the southern annular mode (SAM) at SH midlatitudes in summer are not annular in appearance owing to differences in regional circulation and precipitation impacts. Both station and reanalysis data indicate a trend toward cooler summer temperatures over southeast and south-central Australia and inland areas of the southern tip of Africa. It is also found that since the onset of the ozone hole, there have been significant shifts in the distributions of both the seasonal mean and daily maximum summertime temperatures in the SH midlatitude regions between high and low ozone years. Unusually hot summer extremes are associated with anomalously high ozone in the previous November, including the recent very hot austral summer of 2012/13. If the relationship found in the past three decades continues to hold, the level of late springtime ozone over Antarctica has the potential to be part of a useful predictor set for the following summer’s conditions. The results herein suggest that skillful predictions may be feasible for both the mean seasonal temperature and the frequency of extreme hot events in some SH midlatitude regions of Australia, Africa, and South America. Natural Sciences and Engineering Research Council of Canada (Postgraduate Scholarship) National Science Foundation (U.S.). Frontiers in Earth System Dynamics